Industrial applications of holonic and multi-agent systems : 8th International Conference, HoloMAS 2017, Lyon, France, August 28-30, 2017, Proceedings /: 8th International Conference, HoloMAS 2017, Lyon, France, August 28-30, 2017, Proceedings. (2017) - Unknown
No abstract available